POLEMIK HUBUNGAN KERJA SISTEM OUTSOURCING - Nawawi Nawawi (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2013)
Outsourcing practice is a contentious issue in Indonesia. Pro and contra against outsourcing practice among employers and workers has been increasing and becoming one of a major stumbling block for the establishment of healthy industrial relations in Indonesia. The legalization of outsourcing in the 2003 Labor Law provides legal basis for employers to minimize the risk of companys production cost by rearranging recruitment system through outsourcing. On the other hand, the implementation of outsourcing has adversely affected workers status and welfare. The implementation of outsourcing has weakened the bargaining position of low skilled workers in the labor market. Therefore, there is a growing need to conduct a comprehensive evaluation of the 2003 Labor Law regarding outsourcing and other contentious issues pertinent to the Law, to reach consensus between workers and employers. This paper aims to explain the dispute over implementation of outsourcing related to the 2003 Labor Law. It argues of the urgency of revision of 2003 Labor Law to deal with outsourcing practice in the future.Keywords: Outsourcing, Labor Law, Worker, Employer, Industrial Relation